Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1161/strokeaha.119.025811
|View full text |Cite
|
Sign up to set email alerts
|

Radial Artery Catheterization for Neuroendovascular Procedures

Abstract: Background and Purpose— Radial artery catheterization is an alternate route of access that has started to gain more widespread use for neuroendovascular procedures, and there have been few studies that describe its safety and efficacy. We present our institution’s experience in performing neuroendovascular interventions via a transradial approach, with excellent clinical outcomes and patient satisfaction measures. Methods— We conducted a retrospective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 9 publications
2
72
1
Order By: Relevance
“…In 2018, Snelling et al 22 found a similarly low rate of complications in 148 procedures using a TRA approach; no major complications but 10 (~6%) minor complications were noted. More recently, in 2019, Khanna et al 23 found 10 minor complications in 233 patients with a TRA neuroendovascular procedure. When complications were broken down by procedure type in our study, we found no significant difference in complication rates between TRA and TFA when performed for treatment; however, when analyzing diagnostic and vasospasm angiography procedures, the TFA approach had a 6% complication rate versus a 1% complication rate for the TRA approach (p=0.007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Snelling et al 22 found a similarly low rate of complications in 148 procedures using a TRA approach; no major complications but 10 (~6%) minor complications were noted. More recently, in 2019, Khanna et al 23 found 10 minor complications in 233 patients with a TRA neuroendovascular procedure. When complications were broken down by procedure type in our study, we found no significant difference in complication rates between TRA and TFA when performed for treatment; however, when analyzing diagnostic and vasospasm angiography procedures, the TFA approach had a 6% complication rate versus a 1% complication rate for the TRA approach (p=0.007).…”
Section: Discussionmentioning
confidence: 99%
“…The TRA approach for neuroendovascular procedures has continued to gain traction over the past several years with a wide array of benefits reported, including a reduced risk of severe complications 22 23. However, unlike in interventional cardiology, the use of TRA still remains secondary to a TFA approach for neurointerventional procedures, largely due to the general lack of large studies in this field 4 22.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the indisputable advantages of wrist access, some neurovascular centers have recently accepted the challenge and switched their approach to a transradial access for diagnostic and interventional procedures with great success 1–6…”
Section: Discussionmentioning
confidence: 99%
“…The neurointerventional field has recently adopted the transradial approach for diagnostic angiographies and interventional procedures 1–6. Faster postprocedural recovery, higher patient satisfaction, and fewer access site complications are some of the major advantages of wrist access over the transfemoral approach.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral angiography has seen a recent shift toward transradial access instead of traditional transfemoral access out of concerns for patient preference and safety 1–5. In neurovascular centers across the USA in 2016, up to 4.5% of mechanical thrombectomies for acute ischemic stroke were performed via transradial access 6.…”
Section: Introductionmentioning
confidence: 99%